Pemanfaatan Media YouTube sebagai Media Pembelajaran pada Siswa Kelas XII MIPA di SMA Negeri 1 Tawangsari - Suwarto Suwarto; Ahmad Muzaki; Muhtarom Muhtarom (Universitas PGRI Semarang, 2021)
The Covid-19 virus became the beginning of a change in the face of the world, one of the sectors affected was the education sector. The government through the Ministry of Education and Culture gave a new policy in the form of distance learning. Students carry out learning from home but are still under the supervision of the teacher. Online communication is one of the keys to keep the educational program running well. Therefore, this becomes a new problem where teachers are required to provide interesting learning materials and in accordance with the characteristics of students. Currently, there are many online media platforms that can be used in learning, one of which is YouTube. YouTube is a social media or video sharing website where there are several categories in video groupings such as entertainment, sports, education, and so on. By utilizing this YouTube application as a learning medium, it can improve the quality of learning.